2002
DOI: 10.1063/1.1447194
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of anisotropy in exchange biased Fe/KCoF3 system

Abstract: We used molecular beam epitaxy to deposit a novel ferro-/antiferromagnet (Fe/KCoF3) system on gallium terminated GaAs (100) substrates. We varied the thicknesses of single crystal Fe (001) layers from 1.05 to 3 nm. The antiferromagnetic fluoride, with a thickness of 30 nm, was deposited either in a single-crystal or a polycrystalline form, depending on the deposition conditions. KCoF3 is an antiferromagnet with a Néel temperature of 114 K. Its cubic structure almost perfectly matches the Fe film structure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Simultaneous observation of the FM and AF spins in Co/LaFeO 3 [16] and Co/NiO [17] systems revealed that FM magnetisation is aligned parallel or antiparallel to the in-plane projection of the AF axis in contrast to the usually observed perpendicular coupling consistent with the Koon's model [15]. Uniaxial anisotropy is also detected after deposition of Fe on top of KCoF 3 [18,19]. All these AFs are known to have rather large magnetostriction of the exchange nature (see Table 1).…”
Section: Uniaxial Anisotropy Of Ferromagnetmentioning
confidence: 64%
See 1 more Smart Citation
“…Simultaneous observation of the FM and AF spins in Co/LaFeO 3 [16] and Co/NiO [17] systems revealed that FM magnetisation is aligned parallel or antiparallel to the in-plane projection of the AF axis in contrast to the usually observed perpendicular coupling consistent with the Koon's model [15]. Uniaxial anisotropy is also detected after deposition of Fe on top of KCoF 3 [18,19]. All these AFs are known to have rather large magnetostriction of the exchange nature (see Table 1).…”
Section: Uniaxial Anisotropy Of Ferromagnetmentioning
confidence: 64%
“…Nevertheless, this value will last to choose preferable axis of magnetisation as was clearly observed in the experiments [18,19]. [19] More pronounced effect is expected in Co films, which have rather high magnetostriction and small bulk magnetic anisotropy.…”
Section: Uniaxial Anisotropy Of Ferromagnetmentioning
confidence: 94%
“…Exchange coupling between the uncompensated spins of the antiferromagnet and the ferromagnetically ordered spins introduces a unidirectional anisotropy and a pinning of the ferromagnet, which result in modification of overall magnetic anisotropy, increases coercivity and shifts the hysteresis loop when the structure is cooled in the presence of magnetic field [1][2][3]. All the effects discussed above were observed in a Fe=KCoF 3 system consisting of an ultra-thin ferromagnetic layer and a thicker antiferromagnetic fluoride [4,5]. An interesting feature of this system is that by modification of the growth condition we could produce samples with single crystal or polycrystalline fluorides having different interface structures and consequently different degrees of spin compensation.…”
mentioning
confidence: 79%
“…Further X-ray studies indicated congruent growth of KCoF 3 fluoride with a cubic perovskite structure [4]. The j-scans (in plane rotation) of single crystal fluorides showed distinct [1 1 0] peaks with four-fold symmetry [5].…”
mentioning
confidence: 97%
See 1 more Smart Citation